Aprendizado como potência de agir: uma tentativa na alfabetização - Busato, Fernanda Reginato (My University, 2022)
The literacy theme rehearses with the philosophy of education of difference through an attempt to bring apprenticeship as a power to act to literacy with the research problem that asks: can we approach apprenticeship as a power to act in literacy? Starting from the problematization, the objective is to rehearse the attempt to approach apprenticeship as a power to act in literacy. The research method expresses a conceptual essay composed of three chapters, the first part brings the childhood memories that led to the problematization of the non-learning position from the theme apprenticeship and the power to act; The next one shows learning and its link to literacy pedagogies and representation; the third one is the attempt, through which the study of the power to act of Spinoza's bodies, by Deleuze (2002, 2019), and its capacity to affect in encounters joined the education, and an opening was rehearsed through the approximation of learning as the power to act, thus tracing possibilities in literacy. The attempt affirms apprenticeship as a power to act, that is, apprenticeship that enters the game of affections (DELEUZE, 2002, 2019) and the idea-affection (the body is more affected than it affects another body) allows opening the defense of in the area of literacy investing in the perspective of ethics. [resumo fornecido pelo autor]
O tema alfabetização ensaia junto à filosofia da educação da diferença por meio de uma tentativa de aproximar o aprendizado como potência de agir à alfabetização. A partir da problematização, o objetivo ensaia a tentativa por meio de três capítulos, nos quais a primeira parte traz as memórias de infância que conduziram à problematização da posição de não-aprendizagem a partir do tema aprendizado e a potência de agir; a seguinte mostra a aprendizagem e sua ligação com as pedagogias de alfabetização e a representação; e a terceira e última parte é a tentativa, por meio da qual o estudo da potência de agir dos corpos de Spinoza, por Deleuze (2002; 2019), e sua capacidade de afecção em encontros uniu-se à educação, e ensaiou-se uma abertura, traçando assim, possibilidades na alfabetização. A tentativa afirma o aprendizado como potência de agir, ou seja, o aprendizado que entra no jogo das afecções (DELEUZE, 2002; 2019) e a ideia-afecção (o corpo é mais afectado do que afecta outro corpo) permite abrir a defesa de na área da alfabetização investindo na perspectiva da ética. [resumo fornecido pelo autor]
Keywords: Aprendizagem; Alfabetização; Educação; Learning; Literacy; Education